2018
DOI: 10.1002/aur.1916
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between autism spectrum disorder and intolerance of uncertainty

Abstract: Youth with ASD without co-occurring intellectual disability experience high levels of intolerance of uncertainty (IU), which is related to anxiety. This study found that IU may also have a relationship with certain aspects of ASD, particularly emotion dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 61 publications
1
55
0
1
Order By: Relevance
“…This is because there is often a discrepancy between self-reported and proxy-reported data in relation to autistic individuals (e.g. Vasa et al, 2018) and that individuals are often better-informants of their IoU (Comer et al, 2009). This parallels the approach taken by Osmanağaoğlu et al (2018).…”
Section: The Current Reviewmentioning
confidence: 99%
“…This is because there is often a discrepancy between self-reported and proxy-reported data in relation to autistic individuals (e.g. Vasa et al, 2018) and that individuals are often better-informants of their IoU (Comer et al, 2009). This parallels the approach taken by Osmanağaoğlu et al (2018).…”
Section: The Current Reviewmentioning
confidence: 99%
“…A need for predictability and routine is a key dimension of “intolerance of uncertainty,” which has been identified within a meta‐analysis as a transdiagnostic factor for the development and maintenance of anxiety (Osmanagaoglu, Creswell, & Dodd, 2018) as well as other mental health conditions (Gentes & Ruscio, 2011; Hong & Cheung, 2014). The relationship between intolerance of uncertainty and anxiety in individuals on the spectrum has been explored using quantitative (e.g., Cai, Richdale, Dissanayake, & Uljarevic, 2018; Vasa, Kreiser, Keefer, Singh, & Mostofsky, 2018) and qualitative methods (e.g., Hodgson, Freeston, Honey, & Rodgers, 2017). Although there is clearly a strong relationship between intolerance of uncertainty and anxiety, there is a complex interplay with the sensory sensitivities (Neil, Olsson, & Pellicano, 2016) and emotional dysregulation (Vasa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between intolerance of uncertainty and anxiety in individuals on the spectrum has been explored using quantitative (e.g., Cai, Richdale, Dissanayake, & Uljarevic, 2018; Vasa, Kreiser, Keefer, Singh, & Mostofsky, 2018) and qualitative methods (e.g., Hodgson, Freeston, Honey, & Rodgers, 2017). Although there is clearly a strong relationship between intolerance of uncertainty and anxiety, there is a complex interplay with the sensory sensitivities (Neil, Olsson, & Pellicano, 2016) and emotional dysregulation (Vasa et al, 2018). As parents in the current study identified self‐regulation and sensory difficulties as a barrier to children managing their own anxiety in the community, these areas and their interplay with the autism and anxiety profile warrant further consideration and exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to restricted inhibitory tone in ASD, there is evidence for a general intolerance of uncertainty (Boulter et al 2014;Fujino et al 2017;Vasa et al 2018), and altered performance with environmental uncertainty (Milne et al 2002;Spencer et al 2000). Furthermore, differences have been found in multiattribute decision tasks (Foxe et al 2015;Zaidel, Goin-Kochel, and Angelaki 2015).…”
Section: Choice Patterns Of Those With Autism Will Differ From Neurotmentioning
confidence: 99%
“…Additionally, environmental uncertainty offers an entry-point to understanding neuropsychiatric conditions, such as autism spectrum disorder (ASD). A myriad of findings suggest that the diagnostic signs of behavioral rigidity and sensory abnormalities (American Psychiatric Association 2013) may be related to an intolerance of environmental uncertainty (Foss-Feig et al 2017;Fujino et al 2017;Boulter et al 2014; Van de Cruys et al 2014;Vasa et al 2018). A mechanistic understanding of how hierarchical neural systems handle environmental uncertainty when making decisions can not only provide knowledge as to how the brain functions, but also may produce hypotheses as to the etiology of ASD.…”
mentioning
confidence: 99%